Day 1 Wed, February 19, 2020 2020
DOI: 10.2118/199291-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Organic Acids Roles in Acidizing Operations for Carbonate and Sandstone Formations

Abstract: Hydrochloric acid (HCl) is the acid of choice for acidizing operations in most carbonate formations and is the base acid commonly paired with others such as hydrofluoric (HF) in most sandstone applications. However, high dissolving power, high corrosion rate, lack of penetration, and sludging tendency coupled with high temperature can make HCl a poor choice. Alternatively, weaker and less corrosive chemicals such as organic acids can be used instead of HCl to avoid these issues. The objective of this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…The experiment of acid dissolution for 2 h was carried out at 45 °C (the formation temperature is 45 °C), and the plugging solution system with large-scale dissolution and a small amount of molten rock was preferred. The slow acid solution system used is the following: 10% solid acid (polycarboxylic acid) [23], 10% HEDP (organic phosphoric acid) [24], and saturated EDTA (amino polycarboxylic acid) [25]. The results show that the solid acid and HEDP can differentially dissolve scale samples and rocks, and the dissolution rates are 97% and ~45%, respectively.…”
Section: Retarded Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment of acid dissolution for 2 h was carried out at 45 °C (the formation temperature is 45 °C), and the plugging solution system with large-scale dissolution and a small amount of molten rock was preferred. The slow acid solution system used is the following: 10% solid acid (polycarboxylic acid) [23], 10% HEDP (organic phosphoric acid) [24], and saturated EDTA (amino polycarboxylic acid) [25]. The results show that the solid acid and HEDP can differentially dissolve scale samples and rocks, and the dissolution rates are 97% and ~45%, respectively.…”
Section: Retarded Acidmentioning
confidence: 99%
“…The results showed that both solid acid and HEDP were retarded acids, relatively weak in acidity. The chelation of the two can dissolve more scale and less sand [23]. It has a better plugging removal effect and less formation destructiveness.…”
Section: Retarded Acidmentioning
confidence: 99%
“…Além disso, normalmente não reagem em sua total capacidade ácida devido à liberação de CO2 proveniente da dissolução de carbonatos (CHATELAIN et al, 1976;ALHAMAD et al, 2020); o grau de geração de íons de hidrogênio diminui com o aumento da temperatura e; alto custo se comparado com o HCl (CHANG et al, 2008).…”
Section: Tipos De áCidos Orgânicosunclassified
“…(Kalfayan, 2008). Other alternative chemical recommendations are a chelating agent, organic acid, and organic acid-HF mixtures (Alhamad et al, 2020), (Shafiq, 2018), (Al-Harbi, 2012), (Mahmoud et al, 2011).…”
Section: Introductionmentioning
confidence: 99%